2020
DOI: 10.2174/1568009620666200101094736
|View full text |Cite
|
Sign up to set email alerts
|

Disintegrin Tablysin-15 Suppresses Cancer Hallmarks in Melanoma Cells by Blocking FAK/Akt/ERK and NF-κB Signaling

Abstract: Background: Integrins are crucial anti-cancer therapy targets. We previously showed that tablysin-15 is an integrin antagonist with its Arg-Gly-Asp motif in a novel structural context. Objective: Here we investigated the anti-cancer effects and mechanisms of action of tablysin-15 in melanoma cells. Methods: Cell adhesion, competitive bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We found that ERK expression was attenuated in the REV7‐depleted malignant melanoma cells (Figure 4), indicating that REV7 facilitates cell activities by quantitatively regulating the expression of certain signaling molecules. To support this, several reports have demonstrated that the nuclear translocation of ERK1/2, together with PI3K/AKT activation, affects the viability and motility of malignant melanoma cells by regulating the expression of several genes 27–34 . Further research is warranted to clarify intracellular signaling that interact with REV7 expression in malignant melanoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…We found that ERK expression was attenuated in the REV7‐depleted malignant melanoma cells (Figure 4), indicating that REV7 facilitates cell activities by quantitatively regulating the expression of certain signaling molecules. To support this, several reports have demonstrated that the nuclear translocation of ERK1/2, together with PI3K/AKT activation, affects the viability and motility of malignant melanoma cells by regulating the expression of several genes 27–34 . Further research is warranted to clarify intracellular signaling that interact with REV7 expression in malignant melanoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…These pro-inflammatory mediators are modulated via the transcription factor NF-kB (113)(114)(115)(116). It has also been reported that focal adhesion kinase (FAK) associated with NF-kB regulates the cancer cells capacity of survival, invasiveness, and metastasis (117)(118)(119)(120). Buhrmann and co-workers showed that RES inhibited the TNF-b-induced EMT as demonstrated by suppressing EMT factors (up-modulating vimentin and slug, down-modulating E-cadherin) in colorectal cancer cells through preventing the FAK/NF-kB activation as proved by downregulation of MMP-9 and C-X-C motif chemokine receptor 4 (CXCR4) which are the NF-kB-dependent of tumor-promoting factors (17,18).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Tablysin-15 can inhibit endothelial cell proliferation induced by fibroblast growth factor (FGF) and inhibit angiogenesis in vitro [14] . Deng et al found that Tlysin-15 has anticancer effect on human melanoma cells and binds integrin α V β3 to inhibit proliferation, migration and invasion of tumor cells [15] . Deng et al found that Tlysin-15 binds to αV β3 in vitro to inhibit the proliferation, migration and invasion of breast cancer cell lines [16] .…”
Section: Pharmacological Action Of Tabanusmentioning
confidence: 99%